Efektivitas penggunaan teknik self instruction setting kelompok untuk mereduksi prilaku off task (di luar kegiatan belajar) siswa - Wahyuni, Sri; Neviyarni, Neviyarni; Fitria, Yanti; Anisah, Anisah (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This study aimed to examine the effectiveness of group-based self-instruction techniques in reducing off-task behavior among elementary school students. Off-task behavior, such as talking out of turn, daydreaming, and inattention, remains a common issue that can hinder the learning process. This study employed a quasi-experimental design using a non-equivalent control group design. A total of 40 sixth-grade students participated in the study, consisting of 20 students in the experimental group and 20 students in the control group. The results indicated that the experimental group showed a significant reduction in off-task behavior after the intervention, while the control group did not demonstrate a significant change. Furthermore, post-test comparisons revealed that the experimental group had a lower level of off-task behavior than the control group. In practical terms, the difference in mean scores suggests that the intervention had a strong effect on reducing off-task behavior. In conclusion, group-based self-instruction techniques are effective in reducing off-task behavior and improving student engagement in the classroom.